An eye for an eye - Roop, Peter (Jamestown's American portraits, 2000)
In 1775 fourteen-year-old Samantha, who should be wearing dresses, knows that in britches she can out-hunt her twin and out-sail her older brother near their James River home, but can she use those skills against the British when the American Revolution begins?